4.8k views
5 votes
Solve 3cosx = 2+cosx​

User Chad Mx
by
6.0k points

1 Answer

6 votes

Answer:

x= 0.

Explanation:

1. Write the expression.


3cosx = 2+cosx

2. Divide both sides by 3.


(3cosx)/(3) = (2+cosx)/(3) \\\\(3cosx)/(3) = (2)/(3) +(cosx)/(3) \\ \\cosx=(2)/(3) +(cosx)/(3)

3. Subtract
(cosx)/(3) from both sides.


(3cosx)/(3) = (2+cosx)/(3) \\\\(3cosx)/(3) = (2)/(3) +(cosx)/(3) \\ \\cosx-(cosx)/(3)=(2)/(3) +(cosx)/(3)-(cosx)/(3)\\ \\\\cosx-(cosx)/(3)=(2)/(3)

4. Simplify the fraction subtraction.


(3cosx)/(3) -(cosx)/(3)=(2)/(3)\\ \\(3cosx-cosx)/(3)=(2)/(3)

5. Multiply both sides by 3.


3*(3cosx-cosx)/(3)=(2)/(3)*3\\ \\3cosx-cosx=(6)/(3)\\ \\3cosx-cosx=2

6. Solve the subtraction.


2cosx=2

7. Divide both sides by 2.


(2cosx)/(2) =(2)/(2) \\ \\cosx=1

8. Take
cos^(-1) from both sides.


cos^(-1)(cosx) =cos^(-1)(1)\\ \\x=cos^(-1)(1)\\ \\x=0.

User Aliva
by
5.7k points